Jogo educativo para escolares: uma proposta interativa na consulta de Enfermagem - Fonseca, Arina (2013)
Health education through games is an alternative non-traditional educational practice where nurses work in different environments of their practice. This research aims to study the seizure of the ludic in health education for school age children in the prevention of chronic noncommunicable diseases (NCDs). General Aim: From the knowledge of children, formulate a game shaped playful instrument about healthy habits in health, and specific aims: to describe the risk factors for NCDs to which school age children are exposed in their environments, according to children themselves, and analyze their knowledge about healthy living that can make them co-responsible for their own health. It is a qualitative, descriptive research, the action-research type. The setting was a Military Polyclinic in Niterói. 19 children ranging from 7 to 12 years old who agreed to participate of the study and whose parents signed the free and informed consent form were interviewed. The research was approved by the Ethics Committee under No. 411723. The interviews were recorded and transcribed. Content analysis using Bardin generated two categories: Between the ideal and the real and The environment interfaces to health and noticed that children understand ideal healthy behaviors and those daily practiced, strategies against exposure to harmful habits and influences on behavior. The high incidence of NCDs affects people economy and quality of life; so, to analyze the trend of risk factors and these children knowledge enabled to understand generating interfaces of healthy behaviors. Experiencing situations, children grasp concepts, attitudes, care, causes and consequences and rear knowledge, initial step in prevention. Learning something, children become aware of a new world and formulate hypotheses and concepts structuring a liberating consciousness, endowed with understanding to make choices. Designed categories allowed the making of the product of this research: an educational game on health. It is concluded that health education through a game, in a playful and fun way, where child creates and recreates sharing knowledge and doubts, is an excellent method to work on the improvement of people quality of life, what may achieve excellent results excellent results when associated with other actions that support advances in the lives of these people.